2002
DOI: 10.1176/appi.ajp.159.9.1593
|View full text |Cite
|
Sign up to set email alerts
|

Association of Risperidone Treatment Response With a Polymorphism in the 5-HT2A Receptor Gene

Abstract: These results suggest that variations in the 5-HT(2A) receptor gene may influence individual responses to risperidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 9 publications
6
96
2
Order By: Relevance
“…These inconsistencies may be due to lack of power (modest sample size), differences in pharmacological histories, differences in time on study treatment or methods of response measurement. 26 In addition, as the aforementioned studies were done in Han Chinese 11,13,17 and Korean 14 populations, the SNPs analyzed may have less effect in African-American and white populations. In this analysis, we chose to use only data generated while the subjects received risperidone; however, as olanzapine and risperidone have some similarities in receptor activity, the additional data generated while subjects received olanzapine might have increased the power of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These inconsistencies may be due to lack of power (modest sample size), differences in pharmacological histories, differences in time on study treatment or methods of response measurement. 26 In addition, as the aforementioned studies were done in Han Chinese 11,13,17 and Korean 14 populations, the SNPs analyzed may have less effect in African-American and white populations. In this analysis, we chose to use only data generated while the subjects received risperidone; however, as olanzapine and risperidone have some similarities in receptor activity, the additional data generated while subjects received olanzapine might have increased the power of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 22 SNPs were selected on the basis of prior knowledge of their involvement with response to risperidone or to other antipsychotic drugs. The selected SNPs and genes included ANKK1 (rs1800497 [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Genotyping was performed by Cogenics (Newton, MA, USA) using Sequenom MassARRAY iPlex as previously described. 20 Statistical analysis African-American and white patients who had received at least one dose of risperidone between week 0 and study end (week 12) and who had consented to DNA testing were included in the analysis.…”
Section: Selection Of Snps and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…170 A number of reports have associated a silent 5-HT 2A polymorphism, and a 102-T/C substitution, with response to clozapine and risperidone. 116,121,[123][124][125] This polymorphism is in complete LD with a À1438-G/A promoter polymorphism in Caucasian populations (the extent of linkage may vary in different ethnic groups). The G allele of this last polymorphism shows a lower promoter activity than the A allele 171 and may partly explain the associations with response.…”
Section: Pharmacodynamic Factorsmentioning
confidence: 99%
“…These studies have consistently shown that carriers of the C-allele show greater improvement, especially in regard to negative symptoms. A number of studies reported significant associations between the linked 5-HT 2A A-1438G and T102C receptor SNPs and response to atypical antipsychotics (mostly clozapine), but there are some discrepant results with respect to the risk-alleles for non-responding Arranz et al, 1998a;Arranz et al, 1998b;Joober et al, 1999;Yu et al, 2001;Lane et al, 2002;Hamdani et al, 2005; see also Arranz and de Leon, 2007). In addition, there are several studies reporting that there is no association between the T102C substitution and the therapeutic response to clozapine and other antipsychotics (Masellis et al, 1995;Nothen et al, 1995;Jonsson et al, 1996;Malhotra et al, 1996;Lin et al, 1999).…”
Section: Tph1 = Tryptophan Hydroxylasementioning
confidence: 99%